2007
DOI: 10.1002/bem.20390
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of pulsed 900 MHz GSM radiation on mitochondrial membrane potential and motility of human spermatozoa

Abstract: and Key wordsEjaculated, density purified, human spermatozoa were exposed to 900 MHz GSM mobile phone radiation at two specific absorption rate levels (SAR 2.0 and 5.7 W/kg) and examined at various time points post exposure. Change in sperm mitochondrial membrane potential was analyzed using flow cytometry. Sperm motility was determined by computer assisted sperm analysis (CASA). There was no effect of 900MHz GSM radiation on mitochondrial membrane potential. This was also the case for all kinematic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 22 publications
4
34
3
Order By: Relevance
“…Therefore, change in mitochondrial membrane potential as a result of RF EMF exposure could provide a sensitive marker for sperm fecundity. In a recent study (30) we found no evidence of such an interaction.…”
Section: Introductioncontrasting
confidence: 67%
“…Therefore, change in mitochondrial membrane potential as a result of RF EMF exposure could provide a sensitive marker for sperm fecundity. In a recent study (30) we found no evidence of such an interaction.…”
Section: Introductioncontrasting
confidence: 67%
“…22 Other investigators like Falzone et al found no effect of RF-EMW on mitochondrial membrane potential of spermatozoa and motility at a specific absorbance rate (SAR) of 2 W/kg. 23 However, they showed a decrease in straight-line velocity and beat-cross frequency at an SAR of 5.7 W/kg. In the present study, our objective was to validate the results of several recent epidemiologic studies by establishing a causeand-effect relationship between RF-EMW emitted from a mobile phone in talk mode and changes in semen parameters.…”
Section: Introductionmentioning
confidence: 95%
“…In our study we used unprocessed semen samples, which contain both mature and immature spermatozoa to assess the effect of EMW on sperm function, whereas in a recent study conducted by Falzone et al only mature sperm from the Percoll fraction was used for analysis. 23 It has been suggested that free radical generating capacity may be higher in spermatozoa in the low-density region of the Percoll gradient (immature spermatozoa) compared with the capacity of sperm from the higher-density fraction (mature spermatozoa). 28 In a study conducted by Agarwal et al, both normal donors and patients who are infertile were studied and their effects on exposure to RF-EMW were analyzed.…”
Section: Dna Integritymentioning
confidence: 99%
“…[32] Recently, Falzone et al studied [33] the effect of pulsed 900 MHz radiation on various kinetic parameters and mitochondrial membrane potential (MMP) of purified human spermatozoa (by percoll density gradient). They found significant decrease in straight-line velocity and beat-cross frequency at an SAR of 5.7 W/kg.…”
Section: Effects Due To Exposure To Electromagnetic Radiationsmentioning
confidence: 99%